Review visual attention and spatial memory in building inspection: Toward a cognition-driven information system. (April 2020) - Shi, Yangming; Du, Jing; Ragan, Eric
Abstract: With the increasing complexity of modern buildings, it is becoming more challenging for the professionals in the Architecture, Engineering, and Construction (AEC) industry to effectively digest complex engineering and design information and develop an accurate spatial memory that is critical to their daily tasks. As emerging visualization technologies, such as Virtual Reality, are considered as a promising solution, there is a pressing need to understand the mechanism by which different information visualization methods affect AEC task performance. Cognition literature has discovered a strong relationship between attention and memory development, but little has been done to understand how the visual attention patterns during the design documents review affect the effectiveness of spatial memory in AEC tasks. To fill the knowledge gap, this paper presents a human-subject experiment (n = 63) to test how spatial knowledge is acquired in a building inspection task and how the different visual attention patterns affect the development of spatial memory. Participants were asked to review the design information of a real building on campus. To trigger different attention patterns, they were randomly assigned to one of the three groups based on the forms of information given in the review session, including 2D, 3D, and VR groups. After a brief review session, participants were asked to go to the real building to identify discrepancies (based on memory) that were intentionally inserted by the authors. The inspection performance was used to evaluate the spatial memory development. The results indicate that in general there is a positive relationship between test subjects' visual attention (fixation time) and spatial memory, but the increasing rate varies across the three groups, suggesting that visual context plays a critical role in the development efficiency of spatial memory. The findings also indicate that the visual attention – spatial memory relationship may be mediated by the use of different spatial knowledge acquisition strategies. This study is expected to contribute to the construction information technology literature by setting the cornerstone of a cognition-driven information system that tailors into the spatial cognitive process of AEC professionals.